SELF-RATED HEALTH IN YOUTH WITH EXCESS WEIGHT: A LIFESTYLE AND SOCIAL PERSPECTIVE - Andersson, Erik Karlsson (Research Journal of Nursing and Clinical Practice, 2025)
Childhood overweight and obesity present formidable global public health challenges, with far-reaching consequences for individuals and societies. These conditions are influenced by a complex interplay of genetic, non-genetic, and environmental factors. In developed nations, the prevalence of overweight among adolescents, aged 15-19, exceeds 20% for both girls and boys, with obesity affecting around 8% of this population segment. Notably, adolescents from lower socio-economic backgrounds face a higher risk of overweight and obesity compared to their peers in more affluent areas. The consequences of childhood overweight and obesity are profound, leading to severe health issues and psychosocial complications during childhood and into adulthood. These challenges encompass behavioral and emotional difficulties, reduced socialization, stigmatization, and decreased educational attainment. Furthermore, obesity in early life can set the stage for a range of long-term health and social issues. Understanding the determinants and consequences of childhood obesity is of paramount importance for public health initiatives and interventions